2016
DOI: 10.3171/2015.7.spine141207
|View full text |Cite
|
Sign up to set email alerts
|

Posterior osteosynthesis of a spontaneous bilateral pedicle fracture of the lumbar spine

Abstract: Spontaneous bilateral pedicle fractures of the lumbar spine are rare, and an optimal surgical treatment has not been suggested. The authors report the case of a 50-year-old woman who presented with low-back pain and right leg radiating pain of 1 year’s duration. Radiological studies revealed a spontaneous bilateral pedicle fracture of L-5. All efforts at conservative treatment failed, and the patient underwent surgery for osteosynthesis of the fractured pedicle using bilateral pedicle screws connected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…They inserted bilateral pedicles screws at L5 to reduce the pedicle fractures and then resected the lower aspect of the L5 spinous process to place a rod across the lamina, thus connecting the screws while simultaneously avoiding the need for fusion at adjacent levels. 10 This approach could not be applied in our case because the traumatic mechanism of injury caused a significant amount of instability and kyphotic deformity at multiple levels.…”
Section: Discussionmentioning
confidence: 94%
“…They inserted bilateral pedicles screws at L5 to reduce the pedicle fractures and then resected the lower aspect of the L5 spinous process to place a rod across the lamina, thus connecting the screws while simultaneously avoiding the need for fusion at adjacent levels. 10 This approach could not be applied in our case because the traumatic mechanism of injury caused a significant amount of instability and kyphotic deformity at multiple levels.…”
Section: Discussionmentioning
confidence: 94%
“…However, stress fractures of the pedicle are much less common [9]. Vertebral pedicles are part of the posterior neural arch, and, like the pars interarticularis, are vulnerable to cyclic loads, although fractures of the former occur much more rarely than of the latter [10], mainly due to the fact that the pedicle has greater intrinsic strength and a shorter moment arm from the vertebral body and therefore can resist greater cyclic shear forces [11]. Cyron et al [12] reported 5 pedicle stress fractures compared to 53 pars interarticularis fractures in vertebras subjected to experimental cyclic shear loads.…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral pedicle stress fracture has been clearly described in the literature and is commonly associated with contralateral spondylolysis [13][14][15][16]. On the other hand, bilateral pedicle stress fracture is an uncommon event and has been mostly associated with previous spine surgery [2,[17][18][19][20] and activity-related mechanical stress [11,21,22], although there are other case reports of bilateral pedicle stress fractures without the above-mentioned aetiologies-Kim et al [23] reported the case of a bilateral pedicle stress fracture on the second lumbar vertebra with spondylolisthesis in a 63-year-old female patient in the setting of an ankylosing spondylitis; Sadiq [9] reported the case of a bilateral pedicle stress fractures of the second lumbar vertebra in a 36-year-old patient with a sedentary lifestyle and with no risk factor or inciting event; Han et al [10] also reported a bilateral pedicle fracture of L5 on a 50-year-old female without an inciting event or cause; Doita et al [7] reported 2 cases of bilateral pedicle stress fractures. The first case was a 57-year-old male patient with a lumbar canal stenosis and bilateral pedicle stress fracture on L4.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, bilateral puncture is not required, reducing the operative time and decreasing the radiation frequency. Furthermore, the integrity of the pedicle cortex is maintained, avoiding iatrogenic pedicle fracture and preventing the destruction of the axial or lateral biomechanical stability of the spine [19] …”
Section: Discussionmentioning
confidence: 99%